The Widening Gyre: Images as Central to the Global Village - Mark Smith (Journal of the Assembly for Expanded Perspectives on Learning, 2000)
The image is emerging as the lingua franca of technological culture, both resurrecting characteristics of pre-literate classicism and consolidating the global community.
Keywords: global village; imagery; technology